The Relationship between Area of Necrosis with Degree of Lymphocytes Infiltration in Breast Rattus norvegicus Induced by DMBA - Ainiyah Fairus; Aufar Zimamuz Zaman Al Hajiri; Hidayatul Ulya; Syihabuddin Farid; Lysa Veterini; Mohammad Nasir (Sriwijaya Journal of Medicine, 2022)
Breast cancer is one of the leading causes of death in women in the world. According to WHO, the incidence of breast cancer is about 2.1 million. The high mortality rate is often influenced by various reasons, one of which is the prognosis in patients. The level of lymphocyte infiltration in tumor cell tissue has been shown to correlate with a better prognosis in patients, while necrotic tissue found in breast cancer often shows worse prognostic value. To determine the relationship between the area of necrosis with the degree of infiltration of lymphocytes in the breast of Rattus norvegicus induced by DMBA. Method: True experimental study with post-test only controlled group design method using 40 Wistar strains of female (Rattus norvegicus) mice 12-13 weeks old. The technique for taking uses simple random sampling. Examining 2 variables, namely the dependent variable area of necrosis and the independent variable degree of lymphocyte infiltration. The treated group is injected with subcutaneous DMBA 10 mg/Kg BW between the two lower nipples during the middle of the fifth week with a three-week interval of administration to reach 14 times the total administration. Cancer tissue is taken in the fifth week. Data are analyzed by the Spearman test. Results: This study shows no relationship (P> 0.05) between the area of necrosis with the degree of lymphocyte infiltration. Conclusions: There is no relationship the area of necrosis with the degree of lymphocytes infiltration in breast Rattus norvegicus Induced by DMBA.